Compact hypersurfaces in a locally symmetric manifold - CHEN, Junfeng; SHU, Shichang (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
Let M be an n-dimensional compact hypersurface in a locally symmetric manifold Nn+1. Denote by S and H the squared norm of the second fundamental form and the mean curvature of M. Mathematics Subject Classification (2010): 53B20, 53A10.